2023
DOI: 10.3389/fped.2023.1226524
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal health in children and adolescents

Maria Felicia Faienza,
Flavia Urbano,
Mariangela Chiarito
et al.

Abstract: The purpose of this narrative review was to investigate the key determinants of musculoskeletal health in childhood and adolescence, with particular attention to the role of physical activity. First, we examined the importance of bone modeling and remodeling in maintaining the bone health and the integrity and mechanical characteristic of the skeleton. In addition, we reported the evidence on an appropriate calcium and vitamin D intake, as well as local load variation in achieving proper peak bone mass. Proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…In research on musculoskeletal health in children and adolescents, proteomic and transcriptomic studies have identified the skeletal muscle "secretoma," consisting of several myokines with endocrine and paracrine functions [87]. Additionally, these studies offer a comprehensive overview of the pathobiology of fibrodysplasia ossificans progressiva (FOP), highlighting advances in molecular genetics and proteomic research [88,89].…”
Section: Advancements In Proteomics Related To Rare Bone Diseasesmentioning
confidence: 99%
“…In research on musculoskeletal health in children and adolescents, proteomic and transcriptomic studies have identified the skeletal muscle "secretoma," consisting of several myokines with endocrine and paracrine functions [87]. Additionally, these studies offer a comprehensive overview of the pathobiology of fibrodysplasia ossificans progressiva (FOP), highlighting advances in molecular genetics and proteomic research [88,89].…”
Section: Advancements In Proteomics Related To Rare Bone Diseasesmentioning
confidence: 99%
“…Genetic factors impact skeletal development for approximately 60–80% of people [ 1 ] and numerous loci have been associated with low bone mass by Genome Wide Association (GWA) studies [ 2 ]. Environmental factors, such as diet, in particular, adequate intake of calcium and vitamin D, and physical activity, are responsible for the remaining 20–40% of people [ 1 , 3 ]. Changes in the hormonal status, and particularly the reduction in estradiol both in women [ 4 ] and men [ 5 ], are another great contributor to bone damage, with a great magnitude, especially in late adulthood.…”
Section: Introductionmentioning
confidence: 99%